Lacan and Adolescence: The Contemporary Clinic of the “Sexual Non-rapport” and Pornography - Ouvry, Olivier (Frontiers in Psychology, 2018)
This article explores two clinical phenomena—pornography and conspiracy thinking—that are highly relevant today and can be observed specifically among adolescent boys in the early stages of post-puberty: conspiracy thinking and the viewing of pornographic videos. It shows that the Lacanian concepts of the Real (of puberty) and the sexual non-rapport help us understand the psychopathological aspects of these two phenomena. Watching pornographic material becomes equivalent to a conspiracy theory about the sexual non-rapport; both in fact deny the effect of what puberty introduces as radically new.